Government revenue, quality of governance and child and maternal survival. Issue 16 (20th September 2022) - Hall, Stephen; Lopez, Marisol; Murray, Stuart; O'Hare, Bernadette
ABSTRACT: This paper considers the effect of government revenue and the quality of governance on the under-five and maternal survival rates. A non-linear panel data study was undertaken using annual data for every country in the world. The study's broad conclusion is that while government resources, measured as total revenue received by a country's government, is essential, the quality of governance is even more critical in determining a good outcome for both mother and child.